2000
DOI: 10.1785/0119990113
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Dimensional Dynamics of Dipping Faults

Abstract: Recent two-dimensional dynamic simulations of dip-slip faulting (Niel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 21 publications
(53 reference statements)
12
125
0
2
Order By: Relevance
“…They found systematically lower accelerations of the model surface near the normal faults when compared to strike-slip faults. Similar results have been obtained with numerical models (Shi et al, 2003;Oglesby et al, 1998Oglesby et al, , 2000a. The effect of a shallow weak and creeping zone on ground motions from strike-slip earthquakes has been studied quantitatively using foam models by Brune and Anooshehpoor (1998).…”
Section: Ground Motionsupporting
confidence: 65%
See 2 more Smart Citations
“…They found systematically lower accelerations of the model surface near the normal faults when compared to strike-slip faults. Similar results have been obtained with numerical models (Shi et al, 2003;Oglesby et al, 1998Oglesby et al, , 2000a. The effect of a shallow weak and creeping zone on ground motions from strike-slip earthquakes has been studied quantitatively using foam models by Brune and Anooshehpoor (1998).…”
Section: Ground Motionsupporting
confidence: 65%
“…Shi et al (1998) and Shi and Brune (2005) were able to reproduce and refine the experimental results numerically. Several numerical studies confirmed their results (Oglesby et al, 1998(Oglesby et al, , 2000aMa and Beroza, 2008;Nielsen, 1998;Gabuchian et al, 2017). Gabuchian et al (2014Gabuchian et al ( , 2017 most recently revisited this issue by means of experiments using homalite as a rock analogue.…”
Section: Ground Motionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, this 1-D parameter does not describe potential 2-D complexities in the shape of the landslide distribution area. For example, across-strike asymmetry often exists for thrust faults where the hanging wall may experience larger shaking (Oglesby et al, 2000) and therefore has more intense landsliding over a larger distance (Gorum et al, 2011). This hanging wall effect is difficult to isolate because for dip-slip faults the topography in the hanging wall is usually closer to the earthquake source and also more prone to landsliding due to larger relief and steepness.…”
Section: Directivity and Asymmetry In Landslide Distributionmentioning
confidence: 99%
“…Full-space model is a good approximation for cases in which the faults are buried at some depth (Oglesby et al, 2000;Zhang and Chen, 2006b), but it is invalid for a large number of great earthquakes in which the ruptures run directly to the free surface and there exists strong interaction between the fault and the free surface (see, e.g., Nielsen 1998). In view of this, Aochi and his co-workers approximated the effect of free surface Aochi and Madariga, 2003) by applying the image method (Quin, 1990) and studied dynamic rupture propagation on vertical strike-slip fault system.…”
Section: Introductionmentioning
confidence: 99%